Review of Manifestos for the Future of Critical Disability Studies edited by Katie Ellis, Rosemarie Garland-Thomson, Mike Kent, and Rachel Robertson - Simpson, Amber Hester (Disability Studies Quarterly, 2021)
No abstract available.